Oil Reservoir Detection Using Volume Attributes in Chia Surkh Area, Kurdistan Region, Iraq - Yousif, Faris Haji; Aziz, Bakhtiar Qader; Baban, Ezadin Najmadin (Science Journal of University of Zakho, 2022)
This study includes picking seven reflectors from intense sampling of 3D Seismic survey composed of 40 inlines and 30 crosslines, the distance between the seismic lines is equal to 250m. The study deals with extracting and analysing volume seismic attributes of 3D seismic data of Chia Surkh area. The area is located east of Kalar City, Sulaimani Government, Kurdistan Region, Iraq. The main aim is to determine locations of hydrocarbon accumulation by picking seven horizons as well as studying and analysing both subsurface structure and direct hydrocarbon indicators. The seismic volume attributes are calculated from the original seismic data that consist of (400) inlines and (300) crosslines, and the distance between two adjacent lines is equal to (25m). The seismic attributes used in the current study are, variance edge, curvature, root mean square, envelope and sweetness. Revealed existence of a major anticline, a major fault. As well as two small faults were detected and running parallel to the major fault, while the envelope and sweetness attributes emphasized appearance of several bright spots within Lower Fars, Dhiban, Jeribe and Euphrates Formations, which give quite evidence for accumulation of hydrocarbon. The study concluded that the complete system requires for existence of petroleum is available such as the major anticlinal structure, carbonate rocks as an excellent reservoir rocks and gypsum or (anhydrite) as an optimal cap rock. The existence of hydrocarbon is confirmed by bright spots.